The protective effects of melationin, vitamin E and octreotide on retinal edema during ischemia-reperfusion in the guinea pig retina - Yilmaz, T; Çelebi, S; Kükner, AS (Sage Publications Ltd, 2002)
The purpose of this study is to provide evidence that free radical damage is a component of retinal ischemia-reperfusion (I/R) injury, and to determine whether melatonin, vitamin E and octreotide can protect retina from this injury. METHODS. The right eyes of 50 male guinea pigs weighing 500-600 g were used. The animals were randomly assigned to group 1 (control), group 2 (I/R), group 3 (melatonin + I/R), group 4 (vitamin E + I/R) and group 5 (octreotide + I/R). Groups 3, 4 and 5 received four subcutaneous injections at six-hour intervals for total dosage of 10 mg/kg melatonin, 150 mg/kg vitamin E and 22 mug/kg octreotide respectively. The first dose of each substance was administered 5 minutes before retinal ischemia. Retinal ischemia was induced for 1.5 hours, then followed by reperfusion for 24 hours. Infections of all three substances were repeated at 6, 12 and 18 hours during reperfusion. The animals were killed at 24 hours of reperfusion. Sagittal sections of 4 pm were cut and stained with hematoxylin and eosin for light microscopic evaluation. The average thickness (edema) of the inner plexiform layer for each eye was measured in sagittal sections near the optic nerve and expressed in microns. RESULTS. The efficacy of each compound had the following relationships: melatonin>vitamin E>octreotide in preventing retinal damage by ischemia-reperfusion. The mean thickness of the inner plexiform layer was 13.3 +/- 0.8 mum, 25.9 +/- 2.0 mum, 20.0 +/- 0.7 mum, 21.6 0.7 mum, 23.9 +/- 0.8 mum respectively in the control, I/R, I/R plus melatonin, I/R plus vitamin E and I/R plus octreotide groups. The thickness of the inner plexiform layer in group 1 (control) was significantly less than the other groups (p<0.001). The inner plexiform layer was thicker in the UP group than with I/R plus melatonin, UP plus vitamin E and I/R plus octreotide (all p <0.01). The inner plexiform layer was thicker in the I/R plus octreotide group than the I/R plus vitamin E and I/R plus melatonin groups both (p<0.05). Compared to the I/R plus melatonin group, the inner plexiform layer was significantly thicker in the I/R plus vitamin E group p<0.05). CONCLUSIONS. This study demonstrates a protective effect of melatonin, vitamin E and octreotide on the retina during retinal ischemia-reperfusion injury.
25th Congress of the Turkish-Ophthalmology-Society -- SEP 23-26, 2001 -- IZMIR, TURKEY
Keywords: ischemia-reperfusion injury; retina; melatonin; vitamin E; octreotide